Improvement of Mineral and Bone Disorders After Renal Transplantation. Issue 5 (8th March 2022) - Ferreira, Ana Carina; Mendes, Marco; Silva, Cecília; Cotovio, Patrícia; Aires, Inês; Navarro, David; Caeiro, Fernando; Ramos, Rúben; Salvador, Rute; Correia, Bruna; Cabral, Guadalupe; Nolasco, Fernando; et al.
Abstract : Background: Posttransplant mineral and bone diseases are causes of fractures, and their association with cardiovascular events is being studied. Methods: We analyzed the evolution of biochemical, histological, and imaging parameters pre– and 1 y post–renal transplantation in 69 patients and correlated mineral and bone findings with coronary calcifications. At inclusion and after 12 mo, clinical data and echocardiographic findings were recorded, and laboratory evaluations, radiography of the pelvis and hands, and bone biopsy were performed. Noncontrast cardiac computed tomography was performed during the second evaluation. Results: Serum levels of fibroblast growth factor 23 and sclerostin decreased in all patients, parathyroid hormone levels decreased in 89.8% of patients, bone alkaline phosphatase levels decreased in 68.1% of patients, and alpha-Klotho levels increased in 65.2% of patients. More than half of the patients presented with renal osteodystrophy at both biopsies, but histological findings improved: a significant transition from high to normal or low turnover and no significant differences in volume, mineralization defect, or cortical porosity at the 2 evaluations. Alpha-Klotho, sclerostin, and bone alkaline phosphatase shifts affect bone changes. Neither echocardiographic findings nor vascular calcification scores differed between the 2 points. Both the pretransplant period (dialysis vintage, sclerostin, and low bone volume at baseline) and the maintenance of abnormalities in the posttransplant period (high turnover posttransplant) were the most reliable predictors of the severity of the coronary calcification percentile. Conclusions: Renal transplantation improved bone and mineral abnormalities. The pretransplant period determines the severity of calcification. Abstract :